The Effect of Synthetic Analytical Structural Methods (SAS) on Elementary School Students' Initial Reading Ability - Annisa Yulia Nuri; Faridah Faridah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This research is motivated by the low initial reading skills of grade I students of MIS Al-Khairi, especially in recognizing letters, reading simple syllables, words, and sentences. This study aims to determine the influence of the Structural Synthetic Analytic (SAS) method on the reading ability of grade I students. The research sample comprised 30 students, divided into an experimental class and a control class. Data were collected through oral tests consisting of a pretest and a posttest. Data analysis was carried out using normality tests, homogeneity tests, and independent sample t-tests. The results showed a significant difference between the experimental and control groups (t = -5.619; p < 0.001). More importantly, the SAS method has a substantial influence on students' initial reading ability, with a Cohen's d of 2.05, which falls in the very large effect category. The average posttest score of the experimental group (M = 49.13) was higher than that of the control group (M = 40.33). The SAS method helps students gradually understand the relationships among letters, syllables, words, and sentences, making reading instruction more effective. Thus, the SAS method can be used as an alternative learning strategy to improve the reading skills of elementary school students.”